Sebaran Populasi Tumbuhan Talas (Colocasia esculenta L. Shoot. ) di Desa Karang Intan Kabupaten Banjar - Helin Mardiana; Anang Kadarsah; Erma Agusliani (Bioscientiae, 2022)
Taro (Colocasia esculenta L. Shoot) is a food crop that has the potential as a source of carbohydrates in food diversification. About 10% of the world's population consume taro as food. This type of plant does not require special growing conditions and is an important source of food because the tubers have good nutritional value. This study aims to analyze the density and the distribution of taro population in Karang Intan Village, Banjar Regency, South Kalimantan. The distribution population study was carried out using the plot-making method, each point was made of 3 plots with a size of 5x5 and then calculated the density of taro and its distribution pattern with the morisita index. The results showed that the density value of taro plants in Karang Intan village was 0.15 m2 while in Runjat village it was 0.14 m2. Based on the distribution pattern with a value of 0.58 in Karang Intan and Runjat villages of 0.39 which means the distribution pattern is uniform. The calculated X2 value in Karang Intan and Runjat villages is smaller than X2 table, namely 11.7647 < 47.400 and 16,8125 < 44,958, this means that the distribution pattern is not significantly different.